Influence of ethanol and glycerol concentration over functional and structural properties of zein-oleic acid films - Pena-Serna, Carolina [UNESP]; Lopes-Filho, José Francisco [UNESP] (Elsevier, 2013)
This study was performed in order to determine the effect of the addition of different concentrations of glycerol and ethanol over functional and structural properties of zein-oleic acid films. Films were prepared from zein and oleic acid formulations, containing: 0, 10, 20 and 30% (w/w) of glycerol as plasticizer and 75, 80, 85, 90 and 95% (v/v) of ethanol as zein solvent. Water vapor permeability (WVP) at 4 and 24 C, opacity, water solubility and structural behavior of the film were assessed. The film water barrier properties, WVP and water solubility, were increased when higher ethanol concentration and lower glycerol concentration were used. Furthermore, WVP at 4 C was lower than WVP at 24 C due to the crystalline solid state of oleic acid at lower temperatures. Likewise, opacity, homogeneity and structure of the composite film were improved as ethanol increased and glycerol lowered. © 2013 Elsevier B.V. All rights reserved.
Keywords: Biomaterial; Diffusion; Electron microscopy; Optical microscopy; Surface properties; Thin film; Crystalline solids; Ethanol concentrations; Glycerol concentration; Lower temperatures; Structural behaviors; Water barrier properties; Water solubilities; Water vapor permeability; Biological materials; Biomaterials; Composite films; Ethanol; Glycerol; Oleic acid; Opacity; Solubility; Structural properties; Thin films; Organic solvents